Evaluation of a Safe Motherhood project in Ntcheu district, Malawi - Mseu D; Nyasulu BM; Muheriwa SR (Dove Medical Press, 2014)
Dennis Mseu,1 Betty Mkwinda Nyasulu,2 Sadandaula Rose Muheriwa3 1Nurses and Midwives Council of Malawi, Lilongwe, Malawi; 2Basic Studies Department, Kamuzu College of Nursing, University of Malawi, Lilongwe, Malawi; 3Department of Maternal and Child Health, Kamuzu College of Nursing, University of Malawi, Lilongwe, Malawi Purpose: This study evaluated knowledge and practices of childbearing women on key childcare practices within the Safe Motherhood project, administered by the Ntcheu District Health Office in the Republic of Malawi. The study excluded men and elderly women. Methods: The design was cross-sectional, and utilized quantitative and qualitative data collection and analysis procedures. Data were also collected through review of participant health records. Results: Although the findings showed that all participants (100%, n=400) had general knowledge on maternal and child health care, they did not have comprehensive information, and few mothers were practicing the recommended key child health care practices. Only 42.4% (n=170) knew the appropriate number of visits a woman should make to the antenatal clinic, and very few knew the appropriate time at which to access antenatal care. Only 55% (n=220) of participants breastfed their babies exclusively. Some participants introduced supplementary feeds as early as a month after birth, and not all women delivered at the health facility. Failure to actively involve men and elderly women in maternal and child health issues had a negative impact on women's ability to fully implement key maternal and childcare practices. Conclusion and recommendations: There is a need to actively involve men and elderly women in maternal and child health issues since, in the ideal Malawian context, a child is raised not just by the mother, but also by all who live in the village. Additionally, elderly women are the guardians of members of the childbearing group, and are a traditional reservoir of experience into which young women can tap. There is also a need to engage Community Nurse-Midwives in facilitating women's groups that provide comprehensive antenatal information to mothers, who may then put knowledge into practice. Keywords: health-seeking behavior, key childcare practices, exclusive breastfeeding, men's participation